TRANSPARENCY IN HEALTH SERVICES AT MAJENE REGIONAL GENERAL HOSPITAL, WEST SULAWESI - Solong, Aras; Mahsyar, Abdul; Rahman, Mariati; Alim, Andi (International Journal of Engineering Technologies and Management Research, 2024)
The research objective was to determine the transparency of the implementation of health services and the driving factors for the transparency of the implementation of health services at the Regional General Hospital Majene, West Sulawesi. This research uses a qualitative approach, this type of research is classified as qualitative descriptive research. Data collection through observation made direct observations in the field about events related to the object of research, while interviews conducted interviews with informants to obtain information on implementation transparency issues and driving factors affecting health services, and documentation is research by collecting data in the form of documents such as decrees and regulations. regulations relating to the object of the problem. For analysis starting from data collection, data reduction, data presentation and conclusion. The results of the study show that the transparency of the implementation of health services is transparent because of several indicators, namely, the suitability of service standards, the information system has been published clearly, and the requirements and administration of services are carried out properly and by those set by the hospital. The driving factor that affects the transparency of the implementation of health services at the Majene Regional General Hospital, West Sulawesi, is the availability of Human Resources, namely employees who are tasked with wearing identification and carrying out their duties and responsibilities according to their respective fields, and facilities and infrastructure have been provided to satisfy health services to the community.